FAȚETE ALE UNOR NAUFRAGII: CIVILIZAȚIA SALVATOARE / FACETS OF SOME WRECKS: THE SAVING CIVILIZATION - Lucian Vasile Bâgiu (Incursiuni în imaginar)
The essay is a comparative analysis of the way in which salvation is presented into three novels dealing with shipwrecks and outcasts: Golding’s Lord of the Flies (1954), Tournier’s Friday, or The Other Island (1967), and Coetzee’s Foe (1986). Through the comparative analysis of three novels of the 20th century, the essay highlights how the shipwreck of the representatives of European civilization on an exotic, deserted and uninhabited island leads to a similar solution, of the impossibility of salvation in the framework of the same civilization. The difference in vision from the happy end feature of the Robinson myth established by Daniel Defoe is self-imposed and proves an acute crisis of modern man’s consciousness, but also an aesthetic awareness of the fact that, a few hundred years away from the establishment of the modern myth, European civilization can no longer feed on its own illusions.